DEVELOPMENT AND OPTIMIZATION OF NANOCOCHLEATE-BASED DIOSMIN CARRIERS FOR CANCER TREATMENT - SARDAR SHELAKE; PATIL, SHITALKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This study aimed to develop and optimize diosmin-loaded nanocochleates as a potential targeted delivery system for cancer therapy. Methods: A three-factor, three-level Box–Behnken design was employed to evaluate the effects of phospholipid choline (Factor A), cholesterol (Factor B), and stirring speed (Factor C) on particle size, entrapment efficiency, and polydispersity index (PDI). Diagnostic plots confirmed the model's robustness, with normal distribution of residuals and strong correlation between predicted and actual values. Results: Interaction and 3D surface plots revealed that higher phospholipid and cholesterol concentrations increased particle size and entrapment efficiency, while optimal stirring speed improved uniformity. FTIR spectroscopy confirmed diosmin encapsulation by showing shifts in O–H and C=O stretching peaks, suggesting hydrogen bonding and lipid interactions. Differential Scanning Calorimetry (DSC) further supported the drug's successful encapsulation by revealing the disappearance of diosmin’s endothermic peak, indicating conversion from crystalline to amorphous form. In vitro drug release studies showed sustained release of diosmin from the nanocochleates compared to the pure drug, highlighting enhanced solubility and prolonged availability. Cell cycle analysis using flow cytometry demonstrated that the optimized formulation induced significant cell cycle arrest in MCF-7 breast cancer cells, confirming its potential antiproliferative activity. Conclusion: These findings validate the nanocochleate system as a promising platform for targeted diosmin delivery, offering improved encapsulation efficiency, stability, sustained release, and therapeutic efficacy. The optimized formulation achieved a desirable balance among key parameters, supporting its application in cancer nanomedicine.